Executive function and dietary intake in youth: A systematic review of the literature. (1st August 2019) - Egbert, Amy Heard; Creber, Chloe; Loren, Dorothy M.; Bohnert, Amy M.
Abstract: Despite increasing evidence that childhood obesity may be related to impairments in executive function, the evidence supporting the relation between executive function (EF) and dietary intake, a key factor linked to obesity, is mixed. Although research from the obesity literature often interprets EF as a factor that may influence dietary intake, there is also evidence that dietary intake may influence EF. Drawing on a developmental perspective, this systematic review examines the literature on the link between executive function (i.e., inhibition, working memory, and cognitive flexibility) and dietary intake in youth through the inclusion of cross-sectional, longitudinal, and intervention studies aimed at altering either dietary intake or EF as a way to influence the other. In total, 5650 studies were screened for eligibility. Twenty-six studies met inclusion criteria and were included in the review. Results indicated that the relation between executive function and dietary intake is equivocal. Although there is some support for a cross-sectional relation between executive function and dietary intake, the lack of longitudinal studies makes it difficult to make conclusions about directionality. Findings from intervention studies do not support the effectiveness of short-term manipulations on dietary intake to change subsequent EF, and few intervention studies exist that explicitly aim to "train" EF to change subsequent dietary intake. Furthermore, the wide variety of measures used to assess EF and dietary intake, and the lack of consideration of the role that weight status may play in the relation between EF and dietary intake, make overall interpretation of the literature more difficult. In sum, there is a need for more prospective research examining a variety of ages, domains of EF, and weight statuses, taking into account developmental factors.